MEWUJUDKAN KAMPANYE DELIBERATIF DALAM SISTEM PILKADA SERENTAK 2024 DI INDONESIA - Nurlia Dian Paramita (Bawaslu Provinsi Kepulauan Riau, 2020)
In the implementation of the Pilkada campaign, there is still a conventional model that is not substantive and only makes promises. In the 2015 simultaneous regional elections up to the implement tation of regional elections during the pandemic, the campaign method, face to face remains the main method of choice. Even so, the form of the campaign is more impressed with the top down method that benefits the candidate pair as the superior party. However, the vision and mission ofthe candidate for regional head as the main level of the regional development plan is not able to properly show the narrative symbolizing the characteristics of a prospective leader that is highlighted. Not the quality of the vision, mission and programs that will be implemented. The creation of an agreement in the form of a joint contract between voters and candidates for regional head is a power of legitimacy and credibility that must be carried out actively so that the deliberation politics ofcitizens to their leaders can be formed.